AI Empowers Graphic Design Education: Innovation and Breakthrough - Wang, Yang; Cheng, Lijia; Lu, Fei; Zeng, Ailifei; Lu, Ling (IC-ITECHS, 2024)
In the 1950s, the scientific community first proposed the term "Artificial Intelligence" (AI). Against the backdrop of rapid technological development in the 21st century, the application fields of AI technology are becoming increasingly widespread, penetrating every corner of our work and life. From the perspective of AI's impact on graphic design education, it can provide designers with more inspiration, express more accurately what designers want to convey, and also promote the updating of graphic design course content, thereby continuously cultivating students' comprehensive abilities. AI's integration into graphic design education has led to the development of intelligent design tools that can automatically generate design drafts based on given parameters, thus significantly reducing the time required for the initial design phase. Moreover, AI can analyze trends and user preferences, offering designers insights that can guide their creative process. As a result, the educational curriculum must evolve to include the study of AI algorithms and their applications in design, ensuring that future designers are well-equipped to leverage these powerful tools. This shift not only enhances the efficiency and innovation in the design field but also prepares students for the demands of a future job market that will increasingly rely on AI-assisted design solutions.